Reconstructing Education through Progressivism: A Systematic Review of Recent Evidence - Tri Emelia Rostari; Tanti Permata Sari; Yesmi Elesti; Meli Irzaleny; Sulastri Sulastri (Journal of Social Work and Science Education, 2026)
This study aims to examine how the principles of progressivist educational philosophy are implemented in contemporary learning practices and to analyze their influence on the effectiveness of the teaching and learning process. The review addresses a clear research gap, namely the lack of recent systematic syntheses that critically examine progressivism-based learning within the context of modern educational challenges and empirical classroom practices. This study employs a Systematic Literature Review (SLR) method by analyzing peer-reviewed journal articles published between 2019 and 2024. Relevant studies were retrieved from reputable databases such as Google Scholar, Scopus, and ERIC, using predefined inclusion criteria (focus on progressivist learning, empirical or conceptual relevance to education) and exclusion criteria (non-educational focus, non-peer-reviewed sources, and incomplete data). The results indicate that progressivist approaches consistently enhance learning quality by fostering student activeness, creativity, critical thinking, and intrinsic motivation. The synthesis highlights the central role of teachers as facilitators and the effectiveness of experiential learning in connecting educational content with real-life contexts. The novelty of this study lies in its integrative synthesis of recent literature that positions progressivism not only as a philosophical foundation but also as a practical framework for addressing current educational demands. Practically, the findings imply that educators and policymakers can adopt progressivist principles to design more student-centered, adaptive, and future-oriented learning environments.